Potential and Projection Study of Land and Building Tax - Dhani, Ali Umar (Faculty of Economics and Business UNTAG Semarang, 2023)
Land and Building Tax is one of the regional taxes that has a major contribution to city or regency regional revenues. The purpose of this research is to find out and map the potential income from Land and Building Tax in Semarang City. The research population is all taxpayers in the city of Semarang which includes 16 districts. The sampling technique used in this study used a purposive sampling technique. The data analysis used in this study is a quantitative descriptive analysis using the least squares analysis tool. The results of the study show that the effectiveness, targets, and realization, as well as projected revenue from Land and Building Tax, have increased, except during a pandemic. The Semarang City Government is expected to be able to increase land and building tax revenues, including with an online system and increasing public awareness in paying taxes.